Tranexamic acid reduced blood transfusions in acute burn surgery: a retrospective case-controlled trial - Tapking, Christian; Hundeshagen, Gabriel; Kirchner, Marietta; Fischer, Sebastian; Kneser, Ulrich; Bliesener, Björn (Burns, 2022)
Objective - Early excision and grafting of burn wounds are key for reducing prevalence of infection and sepsis. However, it is associated with massive blood loss and patients frequently require large numbers of blood transfusions. This study aimed to evaluate the effect of tranexamic acid (TXA) on blood transfusion requirements in acute burn surgery. - Methods - Patients admitted to the burn intensive care unit between January 2018 and May 2021 and received TXA before first surgery for wound excision and grafting were matched in a 1:2 ratio to patients that did not receive TXA (confounders age,sex,total body surface area (TBSA) burned). Primary endpoint of the analysis was the total number of transfused units of red blood cells (RBC) intra- and postoperatively up to 48 h. Fresh frozen plasma (FFP) and platelets were evaluated. Endpoints were compared between groups using van Elteren tests adjusting for strata variable age, gender, TBSA. - Results - Twenty-six TXA patients were matched with 52 control patients resulting in similar distributions of gender (77.9%(TXA)vs. 82.7%(control) males, p=0.542), age (51.7±21.3vs.48.3 ±17.4years,p = 0.459) and %TBSA burned (33.5%(IQR34)vs. 38.5% (IQR 30.5),p = 1.000). TXA group received significantly less RBC units intraoperatively (2.5(IQR 2.0)vs.4.0 units (IQR4.0), p = 0.038) and in total (4.0(IQR3.0)vs.6.0(IQR4.0),p = 0.017). TXA patients also received less blood products in general (RBC, FFP, platelets) in each period and in total. We found no significant difference in length of stay (24.0(IQR26.0)vs.33.0 days (IQR 0.5),p = 0.367) or mortality (15.4%vs.21.2%, p = 0.542). - Discussion - This study shows that necessity for blood transfusions in acute burn surgery may be reduced significantly by administration of TXA perioperatively. Randomized-controlled trials are needed to prove these findings.